(untitled) (Biological Sciences - PJSIR, 2016)
Soil seed banks were assessed in three soil layers (L1, from 0 to 2 cm, L2, 2 to 4 cm and L3, 4 to 6 cm depth ) from five microhabitats i.e., Lee-ward side of sand dune (S1), Wind-ward side of sand dune (S2), Clayey area covered with sand (S3), Interdunal sandy area (S4) and Shifting sand dune of site Dingarh Fort area (S5) in Cholistan desert of Pakistan to analyse differences of soil seed bank among these habitats. Ten soil samples were collected from each microhabitat and from each layer i.e., 0-2 cm depth (L1), 2-4 cm depth (L2) and 4-6 cm depth (L3) by using 15´15´6 cm metallic sampler. Consistent differences in seed composition were observed among these microhabitats. Seedling emergence approach was used to assess the soil seed bank of Cholistan desert. Canonical correspondence analysis (CCA) was used for the soil seed bank and the plant species analysis. The microhabitats S3 (Clayey area covered with sand) and S4 (Interdunal sandy area) contributed prominently to the total variance in the species and had maximum density of seed bank and soil layer L1 contained maximum number of seeds.